Konstruksi Hukum Delik Adat Pencurian Benda Sakral dalam Kerangka Sistem Hukum Pidana Indonesia - Subawa, I Wayan Gede; Kemalasari, Ni Putu Yuliana (Belom Bahadat, 2025)
This research departs from the fact that the theft of sacred objects (pratima) in Bali is not merely a violation of general criminal law as regulated in Article 362 of the Indonesian Penal Code (KUHP), but also constitutes an adat (customary) offense that disrupts the spiritual and social balance of Balinese customary communities. Although customary law has been recognized through Article 18B paragraph (2) of the 1945 Constitution of the Republic of Indonesia and Article 2 of the new Penal Code (Law No. 1 of 2023), its application in judicial practice still faces challenges in integrating customary values into the national criminal justice system. The purpose of this study is to construct a legal understanding of the adat offense of sacred object theft within the framework of Indonesia’s criminal law and to analyze the extent to which customary law can be accommodated in the national legal system. The research employs a normative legal method with statutory, conceptual, and case approaches, utilizing secondary data sources such as legislation, court decisions, and academic literature. The results indicate that the existence of customary law as a living law holds a crucial role in realizing substantive justice within a pluralistic society. In the context of sacred object theft, such as pratima, the act is not merely a property crime but also a violation of the community’s spiritual balance, triggering customary reactions to restore social and cosmological harmony. Therefore, the national criminal justice system needs to accommodate customary law values in its enforcement process so that the resulting justice is not only formal but also substantive and contextually aligned with local wisdom. The integration of customary and national law is expected to create a more inclusive, socially just, and culturally rooted judicial system.